Camberwell assessment of need for the elderly (CANE) - Hoe, Juanita ca. 20./21. Jh; Orrell, Martin ca. 20./21. Jh (Cambridge University Press, 2021)
The Camberwell Assessment of Need for the Elderly (CANE) is an internationally accepted tool for assessing the needs of older people. Needs are assessed in twenty-four areas of life and cover a broad range of health, social and psychological domains. Two items that measure the needs of those who care for the older person are also included. The CANE is suitable for use in research, clinical practice and for evaluating health and social services provided to older people. It has been used for over twenty years in a range of settings, populations and countries. This book outlines the evidence for its use in effectively measuring the needs of older people across primary care, community, inpatient and care home settings. Both the full version CANE and short version (CANE-S) are included, along with a detailed manual and scoring guidance. The assessment forms are freely available to download from researchintorecovery.com/can and cambridge.org
Title from publisher's bibliographic system (viewed on 11 Jun 2021)
Keywords: Older people / Medical care; Medical care / Needs assessment